A polymer scaffold with drug-sustained release and antibacterial activity. Issue 6 (12th April 2020) - Wu, Ping; Hu, Shi; Liang, Qin; Guo, Wang; Xia, Yang; Shuai, Cijun; Li, Yongmin
Abstract: Total alkaloids from Semen Strychnine (TASS), as an antibacterial drug, was loaded into polyetheretherketone (PEEK)/polyglycolide acid (PGA) scaffolds fabricated via 3 D printing technology. It focused on studying microstructure, drug-release behavior, antibacterial activity and biocompatibility of scaffolds. Results indicated that TASS had a good physiochemical compatibility with polymer matrix, and a sustained release for longtime in TASS-PEEK/PGA scaffolds. Moreover, the scaffolds manifested antimicrobial activity against E. coli and S. aureus in antibacterial tests and superb biocompatibility in vitro cell culture. These suggested that TASS-PEEK/PGA scaffolds were able to efficiently sustain TASS delivery and were a promising implant for treating bacterial infection. Graphical Abstract: